Antioxidant Activity of Various Extracts and Organic Fractions of Ziziphus jujuba - Nasır Rasool,; Komal Rızwan,; Muhammad Zubaır,; Tahsin Gulzar,; Iftikhar Hussain Bukhari,; Mazhar Amjad Gilani,; Adeela Amjad, (International Journal of Phytomedicine, 2011)
Antioxidant effectiveness of indigenous medicinal plant Ziziphus jujuba shoots extracts and fractions with different polarity solvents (n–hexane, ethylacetate, methanol, chloroform) was assessed for total phenolics content (TPC), total flavonoid contents (TFC), DPPH radical scavenging activity and percentage inhibition of peroxidation in linoleic acid system. The shoots extracts and fractions contained appreciable levels of total phenolic contents 310-823 GAE (mg/100g Dry plant matter) and total flavonoid contents 210- 650 CE (mg/100g of Dry plant matter). The Ziziphus jujuba extracts and various organic fractions also exhibited good DPPH 50% inhibition (IC50) ranges from 23.1µg/mL to 52.5 µg/ml and Inhibition of Peroxidation in Linoleic Acid 20.1 to 70.1%., respectively. Of the Ziziphus jujuba shoots extracts and fractions tested, 100% methanolic extract and 100% chloroform fraction exhibited the maximum antioxidant activity, the results of the present investigation demonstrated significant (p< 0.05) variations in the antioxidant activity. The results of the present comprehensive analysis demonstrated that Ziziphus jujuba shoots extracts and organic fractions are a viable source of natural antioxidants and might be exploited for functional foods and nutraceutical applications